Proteomic profiling of celiac-toxic motifs and allergens in cereals containing gluten - Daly, Matthew E.; Huang, Xin; Nitride, Chiara; Hughes, Christopher; Tanskanen, Jaakko; Shewry, Peter R.; Gethings, Lee A.; Mills, E. N.Clare (American Chemical Society, 2025)
Cereal-based foods can cause immune-mediated adverse reactions, including celiac disease and IgE-mediated allergies, but the potency of different cereal species to cause such reactions appears to vary, with oats being less celiac-toxic and allergenic than wheat. In order to define differences in the immunological potential of wheat, barley, rye, and oats, proteomic profiling of proteins carrying celiac-toxic motifs and allergens has been undertaken. Total protein extracts were subjected to chymotryptic digestion and analyzed using data-independent ion mobility mass spectrometry and a pipeline employing a curated gluten protein sequence database. Depending on the cereal species, 376–2769 proteins were identified, the majority being grain storage proteins. Relative quantitation of proteins containing celiac-toxic motifs showed that they were most abundant and diverse in wheat, with only a limited number, at much lower abundance, identified in oats. Allergens belonging to the seed storage prolamins were the most abundant, while allergens belonging to the α-amylase/trypsin inhibitor family associated with respiratory allergy were of only moderate abundance in comparison. Wheat allergen homologues were identified in other cereal species but at a very low level in oats. These data suggest that the relative risk of oats in the context of both celiac disease and IgE-mediated allergy is low.
Keywords: proteomics; wheat; barley; rye; oats; celiac-toxic motif; IgE epitope